Thermal conductivity and hardened behavior of eco-friendly concrete incorporating waste polypropylene as fine aggregate. (2022) - Ahmed, Sulaiman Nayef; Hamah Sor, Nadhim; Ahmed, Mohammed Akram; Qaidi, Shaker M.A.
Abstract: Waste polypropylene is one of the most common non-biodegradable solid wastes generated by industrial activity in Iraq. Solid waste is one of the several causes having a negative effect on the environment. The issues arise as a result of factors such as the difficulty of recycling waste and restricted reuse. Polypropylene is a significant kind of solid waste that has a negative impact on the environment. The purpose of this study is to determine the effects of using polypropylene as a partial replacement for sand in concrete. This material's effect on the fresh, mechanical, and thermal conductivity properties of concrete was investigated. Six concrete mixtures using polypropylene as a partial substitute for sand were produced at substitution percentages of 0%, 8%, 16%, 24%, 32%, and 40%. The slump, fresh and dry unit weight, compressive strength, and thermal conductivity properties of fresh and hardened concrete were determined. At various rates of concrete production, the results of the experiments demonstrated a decrease in unit weight and compressive strength. Thermal conductivity reduced 49.1% for the mix contained 40% of waste polypropylene and satisfied the lower limit strength for structural purposes.